1994
DOI: 10.1007/bf00203220
|View full text |Cite
|
Sign up to set email alerts
|

The energetics and structure of the hydrogarnet defect in grossular: A computer simulation study

Abstract: Abstract.We have used computer simulation methods to model the structure and energetics of the hydrogarnet defect in grossular. The predicted structure is in good agreement with experimental data. The calculated energy for the reaction of water with grossular to form the hydrogarnet defect is 1.02 Ev (98 kJ mol-1). This low energy of reaction suggests that such defects will be common in garnets where they could play an important role in effecting processes such as atomic transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Using data compiled previously in a study of the energetics of hydrolysis of CaF2 (Catlow, 1977a) we may estimate this quantity as -9.74 eV. The full derivation of this term can be found in Appendix 1 or Wright et al (1993). Finally we have the formation of the defect complex at the vacant Mg site given by:…”
Section: Resultsmentioning
confidence: 98%
“…Using data compiled previously in a study of the energetics of hydrolysis of CaF2 (Catlow, 1977a) we may estimate this quantity as -9.74 eV. The full derivation of this term can be found in Appendix 1 or Wright et al (1993). Finally we have the formation of the defect complex at the vacant Mg site given by:…”
Section: Resultsmentioning
confidence: 98%
“…Over the past several decades, studies using atomistic methods have demonstrated that reliable values can be calculated for defect formation and migration energies. It is worth noting that Wright et al (1994) first used computer simulation methods to model the structure and energetics of the hydrogarnet defect in grossular. Recently, similar studies have been reported by Pigott et al (2015) for MgSiO 3 majorite up to 25 GPa employing both classical atomistic simulations and complementary first-principles calculations.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…As a consequence, it is easier for hydroxyl ions to approach the surface and form chemical bonds with the exposed metal ions. In addition, the tilting of the proton end of the hydrogen atoms of bonded hydroxyl ions, together with the protons adsorbed to the tetrahedron oxygen atoms, can balance the negative surface charge produced by metal ion depletion, as observed before where the tilting of hydrogen atoms balanced the charge introduced by silicon vacancy (Wright et al, 1994). However, because (0 1 0)-water interface inferred from the electron density profile derived from the best fit result, which is plotted in (B).…”
Section: Hydration At the Olivine (0 1 0)-water Interfacementioning
confidence: 84%